THE RELATIONSHIP BETWEEN LEADERSHIP STYLE AND GOVERNMENT APPARATUS PERFORMANCE: AN EMPIRICAL STUDY IN THE DISTRICTS OF TTS, MALAKA, AND KUPANG CITY - Liem, Jhon Sepron D.; Jagi, Kretisana; Hege, Marselinda; Nabu, Yunior; Luruk, Aplonia Dewi; Sabuin, Jefry Y. (Politeknik Negeri Ambon, 2025)
Introduction: This study examines the relationship between leadership style and the performance of government apparatus in three regions: Timor Tengah Selatan Regency, Malaka Regency, and Kupang City.Methods: Quantitative data were collected using valid and reliable questionnaires and analyzed statistically using SPSS. Results: The results indicate that leadership style has a positive and significant effect on apparatus performance in all three areas. Effective leadership styles, particularly democratic and transformational styles, enhance employee motivation, discipline, and productivity. Additionally, competency development and training strengthen this relationship. The study highlights the importance of adaptive leadership styles tailored to an organization's characteristics and local culture in enhancing public service quality. Conclusion and suggestion: Practically, the findings suggest enhancing leadership capacity for village heads and government officials to support optimal apparatus performance Keywords: Leadership style, apparatus performance, village government, public service, employee motivation